FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA PEMBERIAN IMUNISASI DASAR CAMPAK/RUBELLA UMUR 9-12 BULAN DI WILAYAH KERJA PUSKESMAS PENAGAN KABUPATEN BANGKA (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
ABSTRACTRespiratory tract caused by the Measles and Rubella virus. Measles and Rubella are highly contagious. Children and adults who have never been immunized against Measles and Rubella, orwho have never had Measles and Rubella are people who are at high risk of contracting this disease. Based on data from the Penagan Public Health Centre, the total coverage of Measles/Rubellabasic immunization in infants in the work area of the Penagan Public Health Centre in 2018, 2019, and 2020 has decreased and has not reached the MSS target of 95%. The purpose of this study wasto determine the factors associated with the low provision of basic measles/rubella immunization at the age of 9-12 months in the Penagan Public Health Centre, Bangka Regency. This research uses across-sectional design, carried out in the working area of the Penagan Health Center, Bangka Regency. The study population was all mothers who had babies aged 9-12 months as many as 233people with a sample of 77 mothers. Collecting data through interviews with a questionnaire instrument. Data were analyzed by univariate and bivariate analysis by chi square test. The results in therelated factors were knowledge (p=0.002), attitude (p=0.049), family support (p=0.002) and the role of community leaders (p=0.019), the unrelated factor was work (p=0.019). = 0.668) and the mostdominant factor is Family Support with POR = 6.17. It is recommended for puskesmas officers to provide understanding to families, both husbands or from other family members to provide support tomothers, puskesmas officers together with health cadres carry out intensive counseling and socialization to mothers who have children aged 9-12 months. urge the community to take an active role incoming to the measles/rubella immunization service and invite community leaders to be able to announce the place and schedule of immunization services.